Labor Supply Effects of Winning a Lottery - Matteo Picchio; Sigrid Suetens; Jan C. van Ours (Institute for the Study of Labor (IZA), 2015)
This paper investigates how winning a substantial lottery prize affects labor supply. Analyzing data from Dutch State Lottery winners, we find that earnings are affected but not employment. Lottery prize winners reduce their hours of work but they are not very likely to withdraw from the labor force. We also find that the effects of lottery prizes last for several years and materialize predominantly among young single individuals without children.
Keywords: J22; J29; 330; labor supply; income effects; wealth shocks; lottery players